DETERMINATION OF EFFICIENCY BASED ON THE COMPARISON OF ANALYSIS RESULTS OBTAINED ON ASX-1 AND HVI 900 LABORATORY EQUIPMENT (Journal of Science-Innovative Research in Uzbekistan, 2024)
The article describes the advantages and disadvantages of ASX-1 laboratory equipment and HVI 900 modern equipment, their differences, the selection and analysis of the most suitable equipment for a cotton ginning enterprise